2009
DOI: 10.1186/1471-2180-9-253
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the fliY gene encoding a flagellar motor switch protein attenuates mobility and virulence of Leptospira interrogansstrain Lai

Abstract: BackgroundPathogenic Leptospira species cause leptospirosis, a zoonotic disease of global importance. The spirochete displays active rotative mobility which may contribute to invasion and diffusion of the pathogen in hosts. FliY is a flagellar motor switch protein that controls flagellar motor direction in other microbes, but its role in Leptospira, and paricularly in pathogenicity remains unknown.ResultsA suicide plasmid for the fliY gene of Leptospira interrogans serogroup Icterohaemorrhagiae serovar Lai str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 58 publications
(71 reference statements)
1
60
0
9
Order By: Relevance
“…The lack of involvement in disease pathogenesis by the majority of exoproteins is in agreement with the findings of previous studies on L. interrogans virulence genes which have demonstrated that the majority of genes are dispensable for virulence (27,68). Moreover, with the exception of a catalase gene (katE) (34) and a collagenase gene (24), the genes that have been demonstrated to be essential for virulence, such as HtpG (63), Loa22 (69), and those involved in motility (11,12), LPS biosynthesis (13), heme metabolism (70), and adhesion (71,72), have orthologues in the nonpathogenic species L. biflexa. In combination with the finding that the majority of L. interrogans exoproteins have orthologues in L. biflexa, this evidence further supports the theory that L. interrogans evolved from L. biflexa.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The lack of involvement in disease pathogenesis by the majority of exoproteins is in agreement with the findings of previous studies on L. interrogans virulence genes which have demonstrated that the majority of genes are dispensable for virulence (27,68). Moreover, with the exception of a catalase gene (katE) (34) and a collagenase gene (24), the genes that have been demonstrated to be essential for virulence, such as HtpG (63), Loa22 (69), and those involved in motility (11,12), LPS biosynthesis (13), heme metabolism (70), and adhesion (71,72), have orthologues in the nonpathogenic species L. biflexa. In combination with the finding that the majority of L. interrogans exoproteins have orthologues in L. biflexa, this evidence further supports the theory that L. interrogans evolved from L. biflexa.…”
Section: Discussionsupporting
confidence: 77%
“…The bacteria are highly motile, and previous studies have demonstrated that both full motility (11,12) and an intact LPS (13) are required for successful colonization of the host. Unlike the majority of other pathogenic Gram-negative bacteria, Leptospira genomes lack the genes encoding delivery systems, such as type III and IV secretion systems, and classical virulence proteins, such as toxins and effectors (14).…”
mentioning
confidence: 99%
“…It would be interesting to examine the roles of the other Fur homologs in L. interrogans. However, directed mutagenesis is extremely inefficient in pathogenic leptospires, with only two targeted mutations in a pathogenic species of Leptospira being reported to date (16,39). Ongoing screening of our transposon library has not yet yielded mutations of the other Fur homologs.…”
Section: Resultsmentioning
confidence: 99%
“…These avirulent mutants were disrupted in genes of the LPS biosynthesis locus (25) and in genes encoding a heme oxygenase (26), a lipoprotein, Loa22, of unknown function (34), or the flagellar motor switch protein FliY (18). However, only the attenuation of the loa22 mutant was confirmed by complementation studies (34).…”
Section: Discussionmentioning
confidence: 99%